2020
DOI: 10.4068/cmj.2020.56.3.166
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Clinically Applicable Biomarkers for Bipolar Disorder: A Review of Candidate and Proteomic Approaches

Abstract: Bipolar disorder (BD) is a severe psychiatric condition which affects innumerable people across the globe. The etiopathogenesis of BD is multi-faceted with genetic, environmental and psychosocial factors playing a role. Hitherto, the diagnosis and management of BD are purely on empirical grounds as we lack confirmed biomarkers for this condition. In this regard, hypothesis-driven investigations have been unable to identify clinically applicable biomarkers, steering the field towards newer technologies. Innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…To avoid recurrences of mood episodes in BD, lifetime treatment is frequently needed and is essentially pharmacological, using mood stabilizers (e.g., lithium and valproate) or atypical antipsychotics (e.g., quetiapine and aripiprazole); antidepressants are also useful for acute depressive phases [ 2 ]. Notwithstanding advances in neuroscientific research, no clinical or laboratorial biomarker has been clearly identified that allows for an early and accurate diagnosis of BD [ 5 , 6 ]. Thus, a better knowledge of the underlying mechanisms of BD pathophysiology is still an unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid recurrences of mood episodes in BD, lifetime treatment is frequently needed and is essentially pharmacological, using mood stabilizers (e.g., lithium and valproate) or atypical antipsychotics (e.g., quetiapine and aripiprazole); antidepressants are also useful for acute depressive phases [ 2 ]. Notwithstanding advances in neuroscientific research, no clinical or laboratorial biomarker has been clearly identified that allows for an early and accurate diagnosis of BD [ 5 , 6 ]. Thus, a better knowledge of the underlying mechanisms of BD pathophysiology is still an unmet need.…”
Section: Introductionmentioning
confidence: 99%
“…Previous blood/plasma/serum proteomic studies showed that 202 proteins were significantly altered in SZ and 99 in BD ( 6 ). Most of these proteins are involved in glucose homeostasis, lipid metabolism, inflammatory and immune processes, or the role of growth factors ( 6 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous blood/plasma/serum proteomic studies showed that 202 proteins were significantly altered in SZ and 99 in BD ( 6 ). Most of these proteins are involved in glucose homeostasis, lipid metabolism, inflammatory and immune processes, or the role of growth factors ( 6 , 10 , 11 ). While some proteins are likely associated with the disease pathophysiology, others might be related to the non-therapeutic effects of medications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations